Photocatalytic Properties of Zinc Oxide and Graphene Nanocomposites - McLain, Avery Ann (Proceedings of the Wisconsin Space Conference, 2019)
Zinc oxide (ZnO), as a semiconducting oxide, has potential as a photocatalyst due to some of the properties it possesses, including a large excitation energy, deep violet/borderline ultraviolet (UV) absorption at room temperature, and good photocatalytic activity. However, the main issue with using ZnO as a photocatalyst is that it has a rapid rate for the recombination of electron-hole pairs. Since the photoactivity of a catalyst is determined by its ability to create photogenerated electron-hole pairs, having a fast recombination rate can interfere with the reaction process. This issue could potentially be fixed by combining the ZnO with graphene, a carbon-based material. The conjugated structure of graphene enables the separation of charges in the photocatalytic process, so by combining ZnO and graphene the recombination rate could possibly be slowed while retaining the beneficial properties of both materials. Â  This project analyzes the effects of ZnO/graphene nanocomposites on the degradation process of methylene blue dye. This dye breaks down when exposed to solar light, and so the photocatalytic properties of the nanocomposites can be studied by examining how they influence the speed of the reaction process.